The effectiveness of customer relationship through marketing communication in Bank Rakyat Cawangan Jelapang / Nabilah Abdullah - Abdullah, Nabilah (2000)
Bank Kerjasama Rakyat Malaysia Berhad, or better known as Bank Rakyat develop a concept which is 100% Islamic Banking and the biggest cooperative company. Bank Rakyat had achieved great success in the local bank industry by receiving many awards and acknowledgements. Bank Rakyat's marketing plan mostly done by their headquarters through various advertising such as television, billboard, bunting, mail shots, websites and newspaper. However, Bank Rakyat Cawangan Jelapang has to compete with other bank like May Bank, Public Bank or Bank Islam and also with other branches of Bank Rakyat. This is to fulfil their policy to customer use their products or services and increase the sells and because of others factor. All the motive and reason are the factor of need recognition to Bank Rakyat Cawangan Jelapang does the marketing communication in order to maintain customer relationship. The organization has to recognize which marketing communication gives the most effective way to building customer relationship. They also have to identify others factor that could make customer relationship lasting longer. They have to use customer feedback to monitor their success and to improve the services and products available. Moreover, company need to do recognition on the factor could make customer influence by the marketing communication. With the need recognition to retain customer relationship, will help the organization understand more what needed most too satisfied customer thus, stay in using their services.